2020
DOI: 10.1016/j.bandc.2019.103621
|View full text |Cite
|
Sign up to set email alerts
|

Pupil responses to pitch deviants reflect predictability of melodic sequences

Abstract: Humans automatically detect events that, in deviating from their expectations, may signal prediction failure and a need to reorient behaviour. The pupil dilation response (PDR) to violations has been associated with subcortical signals of arousal and prediction resetting. However, it is unclear how the context in which a deviant occurs affects the size of the PDR. Using ecological musical stimuli that we characterised using a computational model, we showed that the PDR to pitch deviants is sensitive to context… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 73 publications
5
34
0
Order By: Relevance
“…Furthermore, arousal signals mediate some of the same cognitive processes that are thought to be triggered by event boundaries, including cognitive control, prediction errors, and attention re-orienting 7 , 18 , 29 31 . Of relevance to the current study, emerging evidence also suggests that arousal responses are sensitive to the structure of temporally extended experiences 32 , 33 . For instance, pupil dilation occurs when a highly organized and repeated sequence of auditory tones suddenly transitions to a randomized sequence of tones, but not during the opposite transition 33 .…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, arousal signals mediate some of the same cognitive processes that are thought to be triggered by event boundaries, including cognitive control, prediction errors, and attention re-orienting 7 , 18 , 29 31 . Of relevance to the current study, emerging evidence also suggests that arousal responses are sensitive to the structure of temporally extended experiences 32 , 33 . For instance, pupil dilation occurs when a highly organized and repeated sequence of auditory tones suddenly transitions to a randomized sequence of tones, but not during the opposite transition 33 .…”
Section: Introductionmentioning
confidence: 72%
“…Similar to other models of statistical learning ( Bröker et al, 2018 ; Harrison et al, 2011 ; Meyniel et al, 2016 ), our memory-constrained PPM model explicitly assumes that listeners represent the unfolding sequences in the form of n-gram sub-sequences of variable length, from which transition probabilities are computed. Previous computational, behavioural and neuroimaging studies Bianco et al, 2020 ; Conklin and Witten, 1995 ; Di Liberto et al, 2020 ; Egermann et al, 2013 ; Pearce et al, 2010 ; Pearce and Wiggins, 2004 ; Pearce and Wiggins, 2006 demonstrated that PPM successfully generalizes to prediction of musical sequences and effectively accounts for psychophysiological responses to melodies. In particular, PPM provided a good match to brain response latencies evoked by transitions between RAN and REG patterns ( Barascud et al, 2016 ; Southwell and Chait, 2018 ), suggesting that listeners may rely on similar memory representations as those proposed by the model.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in synaptic efficacy may also be mediated by fast synchronous interactions, involving spiking inhibitory interneurons equipped with NMDA receptors (Schmidt et al, 2013). Consistent with our results, the precision weighting of prediction errors has been cast as reflecting unexpected uncertainty—i.e., a momentary change in the estimated predictability of the context induced by unexpected events—which has been associated with modulations of pupil diameter and the neuromodulator norepinephrine (Bianco et al, 2020; Dayan & Yu, 2006; Zhao et al, 2019). Thus, a plausible hypothesis is that the enhanced excitability of auditory cortex in response to deviant sounds has its origins in neuromodulation — and concomitant changes in synchronous gain.…”
Section: Discussionmentioning
confidence: 99%